2007
DOI: 10.1111/j.1365-2567.2007.02690.x
|View full text |Cite
|
Sign up to set email alerts
|

Compromised CD4+ CD25high regulatory T‐cell function in patients with relapsing‐remitting multiple sclerosis is correlated with a reduced frequency of FOXP3‐positive cells and reduced FOXP3 expression at the single‐cell level

Abstract: Summary CD4+ CD25high regulatory T cells (Tregs) of patients with relapsing‐remitting (RR) multiple sclerosis (MS), in contrast to those of patients with secondary progressive (SP) MS, show a reduced suppressive function. In this study, we analysed forkhead box P3 (FOXP3) at the single‐cell level in MS patients and controls (healthy individuals and patients with other neurological diseases) by means of intracellular flow cytometry. Our data revealed a reduced number of peripheral blood CD4+ CD25high FOXP3+ T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
279
6
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 329 publications
(332 citation statements)
references
References 49 publications
32
279
6
7
Order By: Relevance
“…Previous studies have shown that patients with multiple sclerosis have Tregs with reduced suppressive function and a retracted TCR repertoire (Viglietta et al, 2004;Haas et al, 2005Haas et al, , 2007Huan et al, 2005;Kumar et al, 2006;Venken et al, 2008). Interestingly, similar observations of reduced Treg function and TCR diversity has been reported in mice deficient in TGFb signalling (Gorelik and Flavell, 2000;Marie et al, 2005Marie et al, , 2006Liu et al, 2008;Ouyang et al, 2010).…”
Section: Tgfb-associated Mirnas Do Not Alter Treg Functionsupporting
confidence: 63%
See 2 more Smart Citations
“…Previous studies have shown that patients with multiple sclerosis have Tregs with reduced suppressive function and a retracted TCR repertoire (Viglietta et al, 2004;Haas et al, 2005Haas et al, , 2007Huan et al, 2005;Kumar et al, 2006;Venken et al, 2008). Interestingly, similar observations of reduced Treg function and TCR diversity has been reported in mice deficient in TGFb signalling (Gorelik and Flavell, 2000;Marie et al, 2005Marie et al, , 2006Liu et al, 2008;Ouyang et al, 2010).…”
Section: Tgfb-associated Mirnas Do Not Alter Treg Functionsupporting
confidence: 63%
“…Although there has been some controversy as to whether patients with multiple sclerosis have a reduced number of Tregs, the majority of studies suggest that the defect is not in number but in function (Viglietta et al, 2004;Haas et al, 2005Haas et al, , 2007Huan et al, 2005;Kumar et al, 2006;Venken et al, 2008). In mice with deficiencies in TGFb signalling, the number of Tregs in adult mice is normal; however, the number of Tregs postnatally is significantly reduced (Marie et al, 2005;Liu et al, 2008;Ouyang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Th17Th1 cells, a subpopulation which secretes both IL-17 and IFN-γ, have also been related to MS pathogenesis (29). Regarding Treg subpopulations, most of the reports found a similar percentage of Tregs in MS patients compared with healthy donors, although a functional impairment has been found in in vitro assays (30)(31)(32). In this context, an increase of the Th17/Treg balance has been associated with higher disease activity and severity (20,33).…”
Section: Th17 and Treg Subpopulationsmentioning
confidence: 96%
“…16 and 17). Furthermore, decreased forkhead box P3 (FOXP3) and cytotoxic T lymphocyte–associated antigen 4 (CTLA‐4) expression is noted in many MS patients 18, 19…”
Section: Ms and Immune Cellsmentioning
confidence: 99%